2016
DOI: 10.1177/1534734616660224
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Patients With Diabetic Foot Ulcer

Abstract: The aim of this study was to describe the characteristics of diabetic foot ulcer (DFU) patients with anemia and assess the relationship between anemia and DFU outcome. A retrospective cohort study was conducted on patients with DFU who attended our hospital from May 2007 to September 2014. All of the variables in the DFU patients with and without anemia were compared. In this study, 353 subjects were included, anemia was present in 236 patients (66.9%). These patients were significantly male, more likely to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…We concluded therefore, that diabetic nephropathy (DN) was a significant determinant of anemia in the index study. This concurs with the findings of Chuan et al [12] who also reported a significant association between anemia and DN among their patients with DFU. Reports from previous studies indicate that anemia complicating chronic kidney disease (CKD) due to diabetes, tended to be more severe and occur much earlier than in nondiabetic CKD [22,23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We concluded therefore, that diabetic nephropathy (DN) was a significant determinant of anemia in the index study. This concurs with the findings of Chuan et al [12] who also reported a significant association between anemia and DN among their patients with DFU. Reports from previous studies indicate that anemia complicating chronic kidney disease (CKD) due to diabetes, tended to be more severe and occur much earlier than in nondiabetic CKD [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…This may account for the higher prevalence of anemia reported. Using Receiver Operating Curve (ROC) analysis, an Hb cut-off of 12.3g/dl (female) and 12.1g/dl (male) in one study, was reported to better identify patients with DFU who are at high risk of adverse outcomes [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, chronic kidney disease is commonly complicated with PAD and uremic neuropathy, which harm the process of wound healing (23,24). Hypoalbuminemia, anemia and edema caused by renal failure may also explain the effect of moderately or severely decreased eGFR on poor ulcer healing in DFU (25,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the duration of diabetes mellitus [ 10 ], a history of previous amputations or foot ulceration [ 11 ], inadequate glycaemic control [ 12 ], a history of hypertension [ 13 ], hyperlipidaemia [ 13 ], the presence of PAD [ 13 ], a history of peripheral neuropathy [ 14 ], a history of osteomyelitis [ 15 ], and wound severity [ 16 ] are independent risk factors for LEA. Furthermore, old age [ 17 ], a history of smoking [ 18 ], anaemia [ 19 ], an elevated white blood cell count [ 20 ], hypoalbuminemia [ 19 ], and the presence of microvascular [ 15 , 21 ] and macrovascular complications [ 22 , 23 ] are all believed to contribute to these risk factors. Nevertheless, different studies have reported different findings, and the published data identifying such predictors for diabetes-related LEA in Saudi Arabia are scarce.…”
Section: Introductionmentioning
confidence: 99%